Penerapan Pembelajaran Al Qur’an Dengan Metode Yanbua - Imam Nurzahidin; Ibnu Muthi (Turabian: Jurnal Pendidikan Islam, 2023)
Madrasah Tsanawiyah Attaqwa Putra Bekasi in learning the Qur'an uses the Yanbu`a method as a compulsory subject and superior program with the result that producing students who have the competence to read the Qur'an properly and correctly compared to elementary schools /other madrasas in the Bekasi area. The purpose of the study was to describe and analyze the planning, implementation and evaluation of learning the Qur'an through the Yanbu`a method at Madrasah Tsanawiyah Attaqwa Putra Bekasi Bekasi. The research method used is field research which is descriptive. The informants of this study were the head of the Tsanawiyah madrasa, the deputy head of the Tsanawiyah madrasa, the Yanbu`a coordinator, the Yanbu`a teacher and students. Data collection techniques using interviews and observation. Data analysis used qualitative analysis, namely data reduction, data presentation, conclusion drawing/verification. The findings of this study are: (1) planning for learning the Qur'an through the Yanbu`a method includes the preparation of teacher resources, learning materials, and learning tools; (2) The implementation of learning the Qur'an through the Yanbu`a method is carried out with two approaches at each meeting, namely the classical and individual approaches (read-listen); and (3) Evaluation of learning the Qur'an through the Yanbu`a method consists of evaluating the learning process and evaluating learning outcomes. Evaluation of the learning process is carried out by monitoring and evaluating teacher performance. Evaluation of learning outcomes includes three assessments, namely: pre-test, daily assessment, assessment of volume increase, ‘pra-imtihan’, and ’imtihan nihaiy’